(untitled) (Baghdad Science Journal, 2005)
The focus of this research revolves around the importance level of sialic acid in the reasoning of cases, including tumors and then evaluate the patient’s response to treatment and its impact on the immune response there are a lot of evidence showing that parts Alkrbu ???????? in peptides sugary and glycoproteins play an important role in Alfalitin life and responsiveness